Beyond the Muscle: Assessing the Efficacy of Oral Creatine Supplementation in Modulating Brain Bioenergetics and Cognitive Performance - Omiecińska , Marta; Miciak, Aleksandra Anna; Węglarz, Aleksandra Karolina; Borowiecka, Patrycja Anna; Adamarczuk, Jagoda Anna; Głuski, Jacek; Urantówka, Nina; Wojtera, Aleksandra; Kaszowska, Karina Barbara; Dąbrowski, Tomasz Piotr; et al. (Quality in Sport, 2026)
Background. The human brain is a metabolically demanding organ, accounting for nearly 20% of the body’s total resting energy expenditure. While creatine has historically been viewed primarily as a supplement for muscle hypertrophy, the discovery of brain-type creatine kinase (BB-CK) has shifted scientific consensus, highlighting its critical role as a neuroprotective metabolite and potential nootropic agent during transient "energy gaps." Aim. This review aims to synthesize current scientific evidence on how oral creatine supplementation can modulate brain bioenergetics and affect overall cognitive performance. Material and methods. This narrative literature review synthesized data from PubMed, Scopus, and the Cochrane Library. The search focused on keywords including “creatine”, “cognitive function”, and “brain bioenergetics”, incorporating systematic reviews, meta-analyses, and randomized controlled trials published in English or Polish, without time restrictions. Results. Current evidence suggests that creatine facilitates the efficient recycling of ATP, which is essential for maintaining neuronal membrane potentials and signal transduction. Supplementation appears to fortify brain bioenergetics, particularly during periods of intense cognitive activity, sleep deprivation, or mental fatigue, helping to bridge the gap when ATP consumption exceeds aerobic synthesis. Conclusions. Oral creatine supplementation emerges as a promising public health strategy to support brain bioenergetics and mitigate cognitive decline. It serves as an effective intervention to enhance cognitive performance under metabolic stress, though further research is warranted to optimize dosing protocols specifically for neurological health.